Nærmere Gud - Larsen, Kasper Bro (Dansk Teologisk Tidsskrift, 2011)
This article examines a basic spatial structure in the religion of the New Testament: Salvation is nearness to God. This theology of nearness breaks with the theology of distance that dominates the Hebrew Bible, and it lies behind the different temporal and eschatological ideas of salvation in the New Testament. Four bodies of texts are taken to demonstrate this: Paul’s letters in terms of spatial participatory language, Ephesians as regards its two-dimensional reconciliation theology, Hebrews with its priestly theology of access to the Holy of Holies, and the Gospel of John regarding its notion of Christ’s permanent indwelling in believers. In all four bodies of text, nearness to God is the main object to be obtained; eschatology, however, is about how and when to acquire it.